Ekologisk kompensation - Att balansera stad och natur - Stenfeldt, Klara Signe (2021)
In Uppsala, Sweden, there is a proposal for a new in-depth comprehensive plan (fördjupad översiktsplan) for southeastern Uppsala that proposes a new train station, a dense development of approximately 21,500 new homes and 10,000–15,000 new jobs. The project area is located in a place with valuable nature, from both an ecological and recreational point of view. When the plan is developed, a large area of forest will be lost. This amounts to a great ecological loss and something that this thesis compensates for in the design of a green wedge proposed the in-depth comprehensive plan.